Nghiên cứu ảnh hưởng của phương pháp chế tạo lên đặc tính và cấu trúc của vật liệu khung cơ kim CuBTC - Thu, Phùng Thị; Hậu, Kiều Xuân; Hồng Lê, Ngô Thị; Hương, Trần Thu; Khuyên, Hoàng Thị; Kiều Giang, Lâm Thị; Anh Thư, Đỗ Thị; Kim Chi, Trần Thị; Hường, Nguyễn Thanh (Vietnam Journal of Chemistry, 2016)
A three-dimensional (3-D) metal–organic framework (MOF) with 3-D channels, named CuBTC (or called also MOF-199 or HKUST-1 Cu3(C9H3O6)2(H2O)3·xH2O), BTC = benzene-1,3,5-tricarboxylate was synthesized by wet chemical method. All of prepared samples were characterized by X-ray diffraction, FT-IR spectroscopy, scanning electron microscopy and BET surface area. The results indicate that CuBTC which was prepared at 110 °C having an octahedral structure and good morphology. The effect of different temperature on their properties was also investigated. Concurrently, these materials CuBTC allow the adsorption of CO using the constant volume method in the condition of my laboratory. Keywords. Metal organic framework, CuBTC, hydrothermal, wet chemical and benzene-1,3,5-tricarboxylate.